Mitochondria Targeted Viral Replication and Survival Strategies—Prospective on SARS-CoV-2 - Gatti, Priya; Ilamathi, Hema Saranya; Todkar, Kiran; Germain, Marc (Frontiers in Pharmacology, 2020)
SARS-CoV-2 is a positive sense RNA coronavirus that constitutes a new threat for the global community and economy. While vaccines against SARS-CoV-2 are being developed, the mechanisms through which this virus takes control of an infected cell to replicate remains poorly understood. Upon infection, viruses completely rely on host cell molecular machinery to survive and replicate. To escape from the immune response and proliferate, viruses strategically modulate cellular metabolism and alter subcellular organelle architecture and functions. One way they do this is by modulating the structure and function of mitochondria, a critical cellular metabolic hub but also a key platform for the regulation of cellular immunity. This versatile nature of mitochondria defends host cells from viruses through several mechanisms including cellular apoptosis, ROS signaling, MAVS activation and mitochondrial DNA-dependent immune activation. These events are regulated by mitochondrial dynamics, a process by which mitochondria alter their structure (including their length and connectivity) in response to stress or other cues. It is therefore not surprising that viruses, including coronaviruses hijack these processes for their survival. In this review, we highlight how positive sense RNA viruses modulate mitochondrial dynamics and metabolism to evade mitochondrial mediated immune response in order to proliferate.